Dressing Up for a BBQ on a Blurry Street: #TheDress Is Not Only Ambiguous in Terms of Illumination But Also in Terms of Scene Content. (June 2019) - Martinovic, Jasna
Explicit or implicit assumptions about the source of illumination are a key determinant of perceived colours from the image of #TheDress. In addition, previous work showed that the extent of the processing of contextual cues in the image may be reduced in blue and black perceivers. This is a brief report of a questionnaire study which focused on the ambiguity of light direction as well as on the ambiguity of the content of #TheDress photograph itself. We replicated previous reports about the importance of perceived light direction: White and gold perceivers were more likely to report light from the back than sideways light. Descriptions of #TheDress image did not relate to perceived colour or light direction, but there were many erroneous reports and a high level of ambiguity. It is highly likely that the ambiguity of image content feeds into the importance of implicit factors that influence perceived illumination as determinants of dress colour.